Results of pressuremeter tests at the Inuvik test site : report of investigation for MacKenzie Valley Pipe Line Research Limited, Calgary, Alberta - Ladanyi, Branko (1973)
ABSTRACT: Scope of the project -- Instrumentation -- Borehole drilling method -- Soil conditions at the site -- Number and type of test -- Results of short-term pressuremeter tests -- Results of pressuremeter creep tests.